Two years of surveillance of influenza a virus infection in a swine herd. Results of virological, serological and pathological studies. (February 2017) - Cappuccio, Javier; Dibarbora, Marina; Lozada, Inés; Quiroga, Alejandra; Olivera, Valeria; Dángelo, Marta; Pérez, Estefanía; Barrales, Hernán; Perfumo, Carlos; Pereda, Ariel; Pérez, Daniel R.
Highlights: Two years surveillance of influenza virus infection in a swine farm are presented. Virus isolation resulted in 6 viruses of the H1N2 subtype δ 2 cluster. Virus shedding was detected in nasal samples from 7, 21 and 42-days old pigs. Long-term active surveillance of IAV in swine is relevant to swine and humans. Abstract: Swine farms provide a dynamic environment for the evolution of influenza A viruses (IAVs). The present report shows the results of a surveillance effort of IAV infection in one commercial swine farm in Argentina. Two cross-sectional serological and virological studies (n = 480) were carried out in 2011 and 2012. Virus shedding was detected in nasal samples from pigs from ages 7, 21 and 42-days old. More than 90% of sows and gilts but less than 40% of 21-days old piglets had antibodies against IAV. In addition, IAV was detected in 8/17 nasal swabs and 10/15 lung samples taken from necropsied pigs. A subset of these samples was further processed for virus isolation resulting in 6 viruses of the H1N2 subtype ( δ 2 cluster). Pathological studies revealed an association between suppurative bronchopneumonia and necrotizing bronchiolitis with IAV positive samples. Statistical analyses showed that the degree of lesions in bronchi, bronchiole, and alveoli was higher in lungs positive to IAV. The results of this study depict the relevance of continuing long-term active surveillance of IAV in swine populations to establish IAV evolution relevant to swine and humans.